Acceptor impurity activation in III-nitride light emitting diodes - Roemer, Friedhard; Witzigmann, Bernd (Applied Physics Letters, 2015)
In this work, the role of the acceptor doping and the acceptor activation and its impact on the internal quantum efficiency (IQE) of a Gallium Nitride (GaN) based multi-quantum well light emitting diode is studied by microscopic simulation. Acceptor impurities in GaN are subject to a high activation energy which depends on the presence of proximate dopant atoms and the electric field. A combined model for the dopant ionization and activation barrier reduction has been developed and implemented in a semiconductor carrier transport simulator. By model calculations, we demonstrate the impact of the acceptor activation mechanisms on the decay of the IQE at high current densities, which is known as the efficiency droop. A major contributor to the droop is the electron leakage which is largely affected by the acceptor doping.
CRIS-Team Scopus Importer:2021-06-11